The Calliopsis (Hymenoptera; Andrenidae; Panurginae) of Chile with the description of a new species - Dumesh, Sheila; Packer, Laurence (Zootaxa, 2011)
Calliopsis rigormortis Dumesh & Packer, new species is described from high altitude in Maule Province in central Chile. It appears to be an Adesmia (Fabaceae) specialist and its specific name refers to its death posture which is similar to that found in other small bees that visit the same genus of plant. A key to the Chilean species of the genus is provided.